The Self-Selection and Effort Effects of Standard-Based Employment Contracts: A Framework and Some Empirical Evidence. - Waller, William S.; Chow, Chee W. (The Accounting Review, 1985)
ABSTRACT: This paper presents a framework for empirical research on the self-selection and effort effects on worker performance of standard-based employment contracts, along with the results of an experiment that tests some hypotheses derived within the framework. The framework examines how personal and contract attributes (or a worker's perceptions of them) affect the self-selection process and how self-selection and effort are interdependent. The experimental results were consistent with these hypotheses: workers select among alternative employment contracts based on their performance capability, the correlation between performance capability and performance incentives in the contract selected is higher in the presence of a controllability filter, and contract selection can explain effort effects.